The many length scales of DNA packaging. Issue 1 (23rd April 2019) - Gilbert, Nick; Allan, James
Abstract : This collection of reviews focuses on the most exciting areas of DNA packaging at the current time. Many of the new discoveries are driven by the development of molecular or imaging techniques, and these are providing insights into the complex world of chromatin. As these new techniques continue to improve, we will be able to answer many of the questions we have now, while likely raising many new ones.